Encapsulated Bleb Excision with Collagen Matrix Implantation Following Failed Ahmed Glaucoma Valve Implantation - Seong Eun Lee, Kyoung Nam Kim, Woo-Jin Kim, Sung Bok Lee, Chang-sik Kim (Korean journal of ophthalmology, 2019)
To investigate the clinical features and surgical outcomes of encapsulated bleb excision with collagen matrix implantation performed in patients with failed Ahmed glaucoma valve (AGV) implantation. Eighteen eyes of 18 patients underwent encapsulated bleb excision and collagen matrix implantation. Patients were divided into two groups by reference to intraocular pressure (IOP) after preoperative ocular massage: group 1, patients who exhibited substantial IOP reductions; and group 2, patients who did not show substantial changes in IOP. Needling was conducted in group 2. The clinical features of the two groups were compared, including IOP changes after ocular massage and needling, AGV status, and surgical outcomes 6 months after surgery. The mean preoperative IOP among the 18 patients was 30.6 ± 5.7 mmHg. After ocular massage, the IOPs decreased by 22 and 26 mmHg in the two patients in group 1 and the 16 patients in group 2 showed a mean IOP reduction of 1.6 ± 2.2 mmHg ( = 0.013). IOPs decreased after needling in group 2 (range, 6 to 30 mmHg; < 0.001). Fibrovascular tissue ingrowth into the AGV was observed in the two patients in group 1 and the same ingrowth was observed in 10 of the 16 patients in group 2. Six months after surgery the mean IOP among the 18 patients decreased significantly (19.1 ± 3.2 mmHg, < 0.001). There was no significant difference in the mean postoperative IOP at 6 months between group 1 (14.0 ± 2.8 mmHg) and group 2 (19.8 ± 2.6 mmHg, = 0.052). Encapsulated bleb excision with collagen matrix implantation resulted in a significant IOP-lowering effect 6 months after surgery. Fibrovascular ingrowth into the AGV was common but did not seem to be a major cause of AGV implantation failure.